Inflammation and the bone-vascular axis in end-stage renal disease. Issue 2 (February 2016) - Viaene, L.; Behets, G.; Heye, S.; Claes, K.; Monbaliu, D.; Pirenne, J.; D'Haese, P.; Evenepoel, P.
Abstract Summary Bone loss and vascular calcification coincide in patients with end-stage renal disease, similar as to what is observed in the general population. In the present bone biopsy study, we provide further evidence that (micro-)inflammation may represent a common soil for both diseases. Introduction Vascular calcification is a common complication of end-stage renal disease (ESRD) and is predictive of subsequent cardiovascular disease and mortality. Mounting evidence linking bone disorders with vascular calcification has contributed to the development of the concept of the bone-vascular axis. Inflammation is involved in the pathogenesis of both disorders. The aim of the present study was to evaluate the relationship between aortic calcification, inflammation, and bone histomorphometry in patients with ESRD. Methods Parameters of inflammation and mineral metabolism were assessed in 81 ESRD patients (55 ± 13 year, 68 % male) referred for renal transplantation. Static bone histomorphometry parameters were determined on transiliac bone biopsies performed during the transplant procedure. Aortic calcification was quantified on lateral lumbar X-rays using the Kauppila method. Results Aortic calcification, low bone turnover, and low bone area were observed in 53, 37, and 21 % of patients respectively. Inflammatory markers were found to be independently associated with aortic calcification (hsIL-6) and low bone area (TNF-α). Low bone area associated with aortic calcification, independent of age, diabetes, and inflammation. Conclusions Low bone area and inflammation associates with aortic calcification, independent of each other and traditional risk factors. Our data emphasize the role of (micro-)inflammation in the bone-vascular axis in CKD.